PENGEMBANGAN ASESMEN ESSAY UNTUK MENGUKUR KETERAMPILAN PEMAHAMAN MATEMATIS SISWA SMA PADA MATERI DIMENSI TIGA - Rani Darmayanti; Agus Setio; Usmiyatun Usmiyatun (Universitas Islam Nusantara, 2023)
One important component in the education system to measure the success and performance of the learning process is assessment activities. The importance of assessment in the learning process can be used as a benchmark for improving the quality of teaching. The purpose of this study was to develop a mathematics learning assessment tool to measure students' abilities in understanding mathematics. The type of development used is related to the model developed by Thiagaran. The study population consisted of five public schools in the city of Pasuruan. The sample of this research was class XII SMA/SMK YALC Pasuruan. The data collection technique used a descriptive test to complete fifteen math questions on three dimensional questions. Data analysis uses validity, reliability, strength, and difficulty. The results of this study indicate that the Essay Test instrument has 12 valid items (3 deleted/deactivated items). Based on the results of this study, we can conclude that the instrument designed to measure students' abilities in understanding mathematics meets valid criteria and can be used in learning